STRUCTURAL PECULIARITIES OF LOWCARBONIZED STEEL AT MODIFICATION ITS SURFACE BY PULSED PLASMA - Ibraev, B.M.; Zhukeshov, A.M.; Gabdullina, A.T. (Recent Contributions to Physics, 2008)
By electronic microscopy and X-ray analyse methods the surface microstructure of lowcarbonized steel after influence of pulse plasma flows was investigated.